Motivation and moral atributes in sport - Vissoci, Joao Ricardo Nickenig; Vieira, Lenamar Fiorese; Oliveira, Leonardo Pestillo de; Vieira, José Luiz Lopes (Journal of Physical Education (Maringá), 2008)
This research’s aim was to analyze the relation between self-determined motivation, sportspersonship and athletic aggression in volleyball players. Participated on this study 54 athletes between adults and youths from both genders. As measure instruments were used: Sport Motivation Scale (1995), Multidimensional Sportspersonship Orientations Scale (1997) and Bredemeier’s Athletic Aggression Inventory (1985). The data collection was performed during training. For the data analysis the Mann-Whitney test, Spearman correlation and Cronbach’s Alpha were used. The data evidenced that overall self-determined motivation was found to be a favorable factor in relation to a positive attitude towards sport’s social conventions, rules and judges influencing on the worry and compromise with the opponent, being able to interfere over the tendency to behave aggressively.